2019
DOI: 10.1016/j.celrep.2019.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Acetic Acid Gustatory Repulsion in Drosophila

Abstract: Highlights d Drosophila exhibit distinct attraction and repulsion to different carboxylic acids d A variant ionotropic receptor (IR7a) is narrowly tuned for rejecting acetic acid d IR7a is required in bitter gustatory receptor neurons for avoiding acetic acid d Acetic-acid-induced action potentials depend on IR7a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 38 publications
5
98
0
Order By: Relevance
“…In the fruit fly Drosophila melanogaster, acids are sensed by gustatory neurons [1,54], and several receptor molecules have been identified that are necessary for their detection: IR76b and IR25a are required for the detection of carboxylic and mineral acids that are attractive and lead to female oviposition [55]. IR76a, IR25a, and IR56d form a receptor involved in behavioral attraction to fatty acids [56], whereas IR7a is required for behavioral aversion to acetic acid [57]. However, functional reconstitution of any of these receptors in a heterologous cell type has not been reported, although IR7a conferred acid responsiveness to sweet-sensing cells within the fruit fly [57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fruit fly Drosophila melanogaster, acids are sensed by gustatory neurons [1,54], and several receptor molecules have been identified that are necessary for their detection: IR76b and IR25a are required for the detection of carboxylic and mineral acids that are attractive and lead to female oviposition [55]. IR76a, IR25a, and IR56d form a receptor involved in behavioral attraction to fatty acids [56], whereas IR7a is required for behavioral aversion to acetic acid [57]. However, functional reconstitution of any of these receptors in a heterologous cell type has not been reported, although IR7a conferred acid responsiveness to sweet-sensing cells within the fruit fly [57].…”
Section: Discussionmentioning
confidence: 99%
“…IR76a, IR25a, and IR56d form a receptor involved in behavioral attraction to fatty acids [56], whereas IR7a is required for behavioral aversion to acetic acid [57]. However, functional reconstitution of any of these receptors in a heterologous cell type has not been reported, although IR7a conferred acid responsiveness to sweet-sensing cells within the fruit fly [57]. In contrast, Otop1 is well established to function as a proton channel in heterologous cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…In insects, GRs expressed in gustatory neurons acts as taste receptors, which are responsible for feeding behaviors (Dunipace et al, 2001;Scott et al, 2001). As a large and highly divergent family of ionotropic glutamate receptors in Drosophila, IRs are subdivided into "antennal IRs, " which are expressed in antennae specifically and mainly involved in olfactory recognition; and "divergent IRs, " which are found in various tissues taking responsible for sensation of taste (Jaeger et al, 2018;Lee et al, 2018;He et al, 2019;Rimal et al, 2019). Various chemosensory associated proteins in insect play diverse functions, such as those listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…This ovipositional preference is mediated by taste sensory neurons in the legs that respond specifically to acids (Chen and Amrein, 2017). Dedicated acid-sensing neurons in the proboscis have not been identified, although acid responses in bitter-sensing neurons have been observed (Charlu et al, 2013; Rimal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%